Noopsychosomatic Disorders in the Light of Empirical Studies (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
A sense of purpose in life is inextricably linked with a firm conviction of exercising control over it, and having one's priorities set straight. Health in turn, is affected by stress, by salutogenetic factors, as presented by A. Antonovsky. Disturbances of sense of purpose in life result in psychosomatic disorders. Hypothesis: there is a relevant statistical correlation between the level of sense of purpose in life and noopsychosomatic disorders. Methods: 1) Crumbaugh-Maholick Purpose-in-Life Test, 2) K. Mausch Questionnaire of Psychosomatic Ailments. Test group: 683 pedagogy students from the University of Szczecin. There is a relevant statistical correlation between the level of sense of purpose in life and psychosomatic disorders. The research results require comparison with other post-soviet countries, as well as democratic ones.